Emergency Department and Overcrowding During COVID-19 Outbreak; a Letter to Editor - Bouillon-Minois, Jean-Baptiste; Raconnat, Julien; Clinchamps, Maelys; Schmidt, Jeannot; Dutheil, Frédéric (Archives of Academic Emergency Medicine, 2021)
Dear editor; Emergency Physicians (EPs) work under extreme stress conditions (1). Overcrowding – defined as hospital beds not being available for several patients who need one – has been a significant public health problem for more than a decade and is the consequence of the increase in health care demand and the decrease in bed spaces and number of staff (2). These parameters increase stress at work, which leads EPs to experience significant stress consequences, a feeling of diminished skills, and loss of time control (3). Many studies are interested in the overcrowding problem, like a recent study by Tangkulpanich et al. who found the predictive factors of revisiting in 48 hours (4).